THE ROLE OF DIAGNOSIS OF CORPORATE CULTURE IN MERGER SCENARIOS - M. Ermoshin (Вестник университета)
The arguments substantiating the need for diagnosis of corporate culture in the planning of the merger are presented. The basic levels of the corporate culture development are identified. The main factors influencing the development of the corporate culture are identified. Various scenarios of corporate merger are considered. The effect of differences in corporate cultures on the process of the merger are described.